Effect and mechanism of the improvement of coastal silt soil by application of organic fertilizer and gravel combined with Sesbania cannabina cultivation - An, Xiaochi; Sun, Menglin; Ren, Kaiyan; Xu, Min; Wang, Zaifeng; Li, Ying; Liu, Hailong; Lian, Bin (Frontiers in Plant Science, 2022)
Jiangsu Province of China has a large area of coastal silt soil (CSS) with poor permeability, high salinity, and poor nutrients, which brings great difficulties to the development and utilization of coastal zones, so that needs to be improved as a matter of urgency. In this study, river-sand, serpentine, and organic fertilizer were used as additives in CSS, and Sesbania cannabina, a salt-tolerant cash crop, was planted in these differently treated soils. Through high-throughput sequencing, analysis of soil physico-chemical properties, and detection of plant growth status, the rhizosphere bacterial diversity of S. cannabina growing in CSS under different treatments and their environmental impact factors were studied, while exploring the effect and mechanism of organic fertilizer combined with gravel as a CSS modifier. The results implied that single application of organic fertilizer could significantly increase the fertility levels of total nitrogen (TN), total organic carbon (TOC) and Avail. P in CSS; then, the application of organic fertilizer with river-sand significantly reduced salt content and alkalinity of soil; meanwhile, in the treatment of single application of organic fertilizer and application of organic fertilizer combined with river-sand, the rhizosphere of S. cannabina enriched the bacterial communities of organic matter degradation and utilization to varying degrees. The soil moisture content and indicators related to saline-alkali (Total salt, electrical conductivity (EC), exchangeable sodium percentage (ESP), Avail. Na and Avail. K, etc.) of the application of organic fertilizer combined with river-sand and serpentine were further reduced significantly, which greatly improved the soil health, and the growth conditions of S. cannabina and the positive development of its rhizosphere bacterial community were promoted. Among them, in the treatment of organic fertilizer combined with river-sand and serpentine, a variety of plant growth-promoting rhizobacteria (PGPR, such as Sphingomonas, Ensifer, and Rhodobacter) and nitrogen-cycle-related bacteria (such as nitrate-reduction-related bacteria, nitrogen-fixing bacteria like Ensifer, and purple non-sulfur photosynthetic bacteria like Rhodobacter) were enriched in rhizosphere of S. cannabina; moreover, the mutual association and robustness of bacterial co-occurrence networks have been significantly enhanced. The results provide a theoretical basis and reference model for the improvement of coastal saline-alkali silt soil.